ATTRACTIVE LEARNING: SEBAGAI UPAYA MENGATASI KEJENUHAN BRAHMACARI DALAM PEMBELAJARAN DI PASRAMAN NONFORMAL PASCA WABAH COVID-19 - I Putu Swana (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
This study aims to study scientifically the attractive learning used to overcome Brahmacari boredom during learning activities in Non-Formal Pasraman after the Covid 19 outbreak. The method used in this research is descriptive qualitative with a phenomenological approach through participant observation data collection, covert interviews, and documentation. Furthermore, the data obtained is reduced, verified, presented, and drawn conclusions. The results of the study found that Attractive Learning in the learning process at Pasraman involves the use of collaborative and varied methods, a fun, joyful and impressive learning atmosphere and places for learning that must be varied or not only in the classroom but also outside the classroom (outdoor learning). There are several choices of methods that can be used to support the implementation of attractive learning in Pasraman, namely: 1) Role Playing Method; 2) Active Debate Method; and 3) Outdoor Learning Methods/Learning Outside the Classroom. The implications of attractive learning in non-formal Pasraman are: 1) Establishment of emotional closeness between Brahmacari and Acarya and between Brahmacari and his colleagues; 2) The learning atmosphere becomes more active, fun and less boring; 3) The growth of Brahmacari's motivation to return to the Pasraman.